The Students' Readiness to Continue Education to The Higher Education and Its Implications in Guidance and Counseling Services - Syakira, Aisya; Syukur, Yarmis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the fact that many students are not yet ready to continue their education to college. Students' unpreparedness can be seen from the low desire of students to continue their education to college. This study aims to describe students' readiness to continue their education to college based on aspects: 1) achievement, 2) behavior, 3) motivation, 4) social engangement, 5) family circumstances, 6) school characteristics. The research method used is a quantitative method with a descriptive approach. The population this study was grade XII students of SMA N 1 Koto Balingka Pasaman Barat, with a research sample of 189 students selected using a purposive sampling technique. Data were obtained using the student readiness instrument to continue their education to college. Data were processed using descriptive statistical techniques. The results of the study showed that the readiness of students to continue their education to college: 1) overall is in the high category of 63%, 2) achievement is in the high category of 46%, 3 behavior is in the high category of 51%, 4) motivation is in the high category of 44%, 5 social engangement is in the low category of 30%, 6) family circumstances is in the high category of 46%, 7) school characteristics is in the high category of 41%. This means that most students already have good readiness to continue their education to college. It is hoped that students can prepare themselves to continue their education to college and utilize the BK services at school optimally.